2019
DOI: 10.3390/nu11112758
|View full text |Cite
|
Sign up to set email alerts
|

Natural Choline from Egg Yolk Phospholipids Is More Efficiently Absorbed Compared with Choline Bitartrate; Outcomes of A Randomized Trial in Healthy Adults

Abstract: Choline is a vitamin-like essential nutrient, important throughout one’s lifespan. Therefore, choline salts are added to infant formula, supplements and functional foods. However, if choline is present in a natural form, e.g. bound to phospholipids, it may be more efficiently absorbed. The study’s aim was to evaluate if choline uptake is improved after consumption of an egg yolk phospholipid drink, containing 3 g of phospholipid bound choline, compared to a control drink with 3 g of choline bitartrate. We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
1
20
0
3
Order By: Relevance
“…It was shown before that levels of free choline were similar after the intake of phosphatidylcholine and choline bitartrate but TMAO showed higher levels after the intake of choline bitartrate [ 21 ]. Others demonstrated that plasma choline levels were higher after the intake of phosphocholine compared to levels after the intake of choline bitartrate [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown before that levels of free choline were similar after the intake of phosphatidylcholine and choline bitartrate but TMAO showed higher levels after the intake of choline bitartrate [ 21 ]. Others demonstrated that plasma choline levels were higher after the intake of phosphocholine compared to levels after the intake of choline bitartrate [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This energy barrier is created by the presence of an emulsion film, which is formed at the surface of the drops. This film is the main factor for stabilizing the emulsion and may consist of one or more molecular layers of the emulsifier (mono-or poly-molecular films) [27].…”
Section: Discussion Of Results Of Studying the Efficiency Of Using Egmentioning
confidence: 99%
“…It was found in [25][26][27] that phospholipids with unchanged native properties have high physiological activity. In this connection, their use is beyond solving only technological tasks.…”
Section: The Aim and Objectives Of The Studymentioning
confidence: 99%
“…In addition, the GPC and CC groups had significantly lower liver PL contents than the control group (Table 1). PL-derived choline is absorbed in the small intestine more efficiently than free forms of choline [13,14], resulting the former having a higher bioavailability. PC, which is synthesized from choline, is known to constitute the outer layer of the cell membrane lipid bilayer [5].…”
Section: Effects Of Dietary Pc Gpc and CC On The Growth And Metabolic...mentioning
confidence: 99%
“…Based on the above-mentioned studies into TMAO, the intake of PC or PC-rich foods has been suggested to be harmful to human health. On the other hand, choline in PC has been reported to be absorbed more efficiently than free choline [13,14], suggesting that choline in PC may be less susceptible to catabolism by gut microbiota than free choline. Taken together, the question as to whether dietary PC exerts a beneficial effect on CVD remains unclear.…”
Section: Introductionmentioning
confidence: 99%